UPAYA ORGANISASI SEKOLAH DALAM MENINGKATKAN KINERJA GURU - KESUMA RAHMAN, RIZKY (Jurnal E-Bis (Ekonomi-Bisnis), 2017)
The focus of the problem in this study examines the factors that play a role in improving teacher performance in the city of Bandung. In this study the performance of teachers can be determined by the principal managerial leadership (planning, communication, organizing, supervision). This study aims to find out, obtain a description and analysis of the effectiveness of managerial leadership of principals, teacher performance, and measure the effect of effectiveness of managerial leadership of principals on teacher performance. This research is done by using quantitative approach with survey method. The design of this study is grouped into descriptive and verification research to analyze the causality relationship between the variables studied. Samples in this study were 3 SMKN in Bandung and Primary data source obtained from questionnaires to 271 respondents. The result of descriptive analysis shows that the overall effectiveness of managerial leadership of headmaster and teacher performance is good, but still not optimal so that required improvement of performance, especially dimension can mingle effectively, development of pedagogic ability, financial compensation.